2012
DOI: 10.1167/iovs.11-9367
|View full text |Cite
|
Sign up to set email alerts
|

Education Is Positively Associated with Macular Pigment: The Irish Longitudinal Study on Ageing (TILDA)

Abstract: PURPOSE. The three carotenoids lutein, zeaxanthin, and mesozeaxanthin, are found at the macula and referred to as macular pigment (MP). This study was undertaken to investigate determinants of MP in a large randomly selected sample from the Republic of Ireland (as part of The Irish Longitudinal Study on Ageing [TILDA]).METHODS. MP optical density (MPOD) was measured using customized heterochromatic flicker photometry in 4373 participants. Sociodemographic and self reported health data was obtained using comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…These include: education (to a maximum of age 11-12 years), mid-life hypertension, mid-life obesity, hearing loss, late-life depression, diabetes, physical inactivity, smoking, and social isolation. Importantly, educational attainment is strongly correlated with socio-economic status, which in turn is associated with better health outcomes (e.g., physical activity [7], tobacco use [8], and healthier diets [9]. There is a growing body of evidence that good nutrition is important for optimal cognition [10] and maintenance of cognition [11] and is also associated with reduced risk of Alzheimer's disease (AD), the most common form of dementia, in later life [12].…”
Section: Introductionmentioning
confidence: 99%
“…These include: education (to a maximum of age 11-12 years), mid-life hypertension, mid-life obesity, hearing loss, late-life depression, diabetes, physical inactivity, smoking, and social isolation. Importantly, educational attainment is strongly correlated with socio-economic status, which in turn is associated with better health outcomes (e.g., physical activity [7], tobacco use [8], and healthier diets [9]. There is a growing body of evidence that good nutrition is important for optimal cognition [10] and maintenance of cognition [11] and is also associated with reduced risk of Alzheimer's disease (AD), the most common form of dementia, in later life [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, a greater percentage of patients with diabetes had cataract (13.83%) compared with controls (6.51%), (p < .0001). Cataract status does not appear to relate to MPOD levels among non-diabetic individuals, 38 suggesting a relationship that is particular to cataract in the presence of Type 2 diabetes, which may impact MPOD levels in this patient group. To our knowledge, this is the first study to report an association between low MPOD and the presence of cataract in diabetes.…”
Section: Discussionmentioning
confidence: 91%
“…Our finding that hypertensive participants with diabetes had significantly lower MPOD compared to normotensive participants with diabetes is important given that hypertension is an established risk factor for the development and progression of DR. 37 The association between MP and hypertension is not well documented; however, one study has reported a link between lower MPOD and a self-reported diagnosis of high blood pressure. 38 Chronic hypertension causes vascular endothelial shear stress and circumferential wall stress. 39 This, in turn, leads to endothelial damage, increased ROS production and activation of inflammatory cascades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher BMI (114) and higher body fat percentage (101) have both been linked with an increased risk of AMD. Studies have reported an inverse relationship between adiposity and BMI and MPOD (99,115) , with the observed relationships largely attributable to participants with a BMI > 29 kg/m 2 (99) . One study found that higher body fat percentage, even within relatively healthy limits, was associated with lower retinal tissue lutein and zeaxanthin status (116) , suggesting that adiposity may affect the nutrient status of the retina.…”
Section: Type 2 Diabetes Macular Pigment Optical Density and Adiposimentioning
confidence: 99%